Respon Kecernaan Bahan Kering dan Ukuran Tubuh Kambing Peranakan Etawah Jantan Terhadap Pemberian Bungkil Inti Sawit - Asril Asril (Jurnal Agripet, 2007)
ABSTRACT. A Study on dry matter digestibility and body sizes of Peranakan Etawah male goat given palm kernel cake (PKC) condukted at the experimental farm of Agriculture Fakulty of Syiah Kuala University. Twelve Peranakan Etawah male goats about 10-17 kg live weight were used in the experiment. randomized block design with 3 clocks and 4 treatments consists of R0 (without PKC) R1 (100 g PKC), R2 (200 g PKC), and R3 (300 g PKC) was applied in this experiment. Parameters measured were dry matter degestibility, crude protein degestibility,crude fiber degestibility, body length, chest gird, and shoulder heinght. The result showet that PKC singnificantly (P0.01) affected crude protein and significantly (P,0.05) affected crude fiber digestibility, body length and chest gird of Peranakan Etawah male goats. However, Peranakan Etawah male goats given PKC have no response on dry matter digestibility and shoulder height.